Sistem Pendukung Keputusan Penentuan Jenis Obat Yang Layak di Konsumsi Ibu-Ibu Hamil Dengan Metode Preference Selection Index - Br. Tarigan, Nera Mayana; Sihotang, Amran; Tarigan, Edy Suramana; Fitria, Harpingka (STIKOM Tunas Bangsa Pematangsiantar, 2021)
This research is a decision support system for determining the types of drugs that are appropriate for consumption by pregnant women using the Preference Selection Index (PSI) method. The Preference Selection Index (PSI) method is used to determine the types of drugs that are suitable for consumption by pregnant women based on criteria. The results of this study are a decision supporter for determining the types of drugs that are appropriate for consumption by pregnant women, the results of this system are only as initial recommendations to pregnant women in determining drugs that can be consumed without replacing the role of the real doctor because drugs from diseases Pregnant women who are more advanced still need expert doctors in handling them. From the results of the research that has been carried out, to apply the preference selection index method in determining the types of drugs that are suitable for consumption by pregnant women, 5 criteria are set, namely fat solubility, degree of ionization, molecular size, protein binding, dose. So according to the results of the analysis that has been carried out, drugs that are suitable for consumption by pregnant women are Paracetamol with an analytical value of 0.9758. To build a decision support system in determining the types of drugs that are suitable for consumption by pregnant women, the researchers first designed use case diagrams, class diagrams, databases, and built a system with PHP and MYSQL programming as the database.